2021
DOI: 10.1186/s12885-021-08913-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, mortality and survival in malignant pleural mesothelioma before and after asbestos in Denmark, Finland, Norway and Sweden

Abstract: Background Malignant pleural mesothelioma (MPM) is a rare but fatal cancer, which is largely caused by exposure to asbestos. Reliable information about the incidence of MPM prior the influence of asbestos is lacking. The nationwide regional incidence trends for MPM remain poorly characterized. We use nationwide MPM data for Denmark (DK), Finland (FI), Norway (NO) and Sweden (SE) to assess incidence, mortality and survival trends for MPM in these countries. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…We speculate that the pre-ban MR of the ‘early-banned countries’ was also in the upper range of that of the ‘banned & identified’ countries. This speculation is supported by our observation that the pre-ban standardised incidence rates of male pleural mesothelioma in the early-banned countries of Denmark, Norway and Sweden were higher than or similar to that of Finland, 29 which had an upper range pre-ban MR of the ‘banned and identified’ countries. Thus, the associations of asbestos bans with mesothelioma MR and identification found in this study would likely be strengthened if we could include the ‘early-banned’ countries in the main analysis.…”
Section: Discussionmentioning
confidence: 53%
“…We speculate that the pre-ban MR of the ‘early-banned countries’ was also in the upper range of that of the ‘banned & identified’ countries. This speculation is supported by our observation that the pre-ban standardised incidence rates of male pleural mesothelioma in the early-banned countries of Denmark, Norway and Sweden were higher than or similar to that of Finland, 29 which had an upper range pre-ban MR of the ‘banned and identified’ countries. Thus, the associations of asbestos bans with mesothelioma MR and identification found in this study would likely be strengthened if we could include the ‘early-banned’ countries in the main analysis.…”
Section: Discussionmentioning
confidence: 53%
“…The peak incidence of mesothelioma in Finland was reported to have occurred in 2006, and this country was one of the rst in Europe to implement a law outlawing the use of asbestos early in 1992 (17). Moreover, Sweden was among the rst nations in the world where the incidence of MPM began to decline very early in 1995 (17). Although MM mortality in the Netherlands was predicted to peak around 2020, a recent analysis suggested that MM incidence peaked earlier in 2010 (15,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…MPM is an aggressive tumor associated with a low 5-year survival rate (≤10%). 23 24 This study was conducted prior to the recent approval of an immunotherapy regimen, and pemetrexed and platinum chemotherapy was a first-line standard of care for patients with unresectable MPM. 24 Several studies support rechallenge with a platinum plus pemetrexed regimen in patients with mesothelioma following an initial favorable response.…”
Section: Discussionmentioning
confidence: 99%